(3TQM GdeYdbGJ GdSHYs - (3MSjf Hf CMeO Hf MSjf GdRhRfj, CHh YHO Gddg,J (B486 (3g` s ((3eMO Hf CHj GdaVd GdUGjYi GdHjgbi s)
(3ChdgG (B:s
(3bGd GdbGVi GdCeGe CHh YHO Gddg gPG TQM GdbUGFO GdSHY , CedjJg Ydi MO GdEjLGR hGdGNJUGQ Ydi MSH eG GbJQM Ydi s
(3BNQgG (B:s
(3hgh GdQH hGdTgjO Ydi jhe GdMjGQjf hGdjdGA HdGA Je GdcJGH HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQ CjVG GdLRA GdChd HQbe (B551 (3COHs
(3cJH GdTYQ HGdMeQIs
(3eYGQVI HfSNI UMjMI ebQhAIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs